Go Slow and Curvy - sohn, dehyun. author. aut Link
XI, 176 p. 56 illus., 51 illus. in color.
Keywords: This book introduces readers to the concepts of sustainability and philosophy of slowness for the management of public entities such as cities or regions. While many urban communities face economic challenges that clearly show the limitations of growth and ever-increasing speed, this book explores an alternative, thought-provoking standpoint in five chapters. The first chapter explains the importance and essence of slowness, smallness and sustainability for public organizations, while the second addresses the concept of “slow life” in an emotional society. Chapter three examines the issue of “slow management” and presents arguments for the value of small businesses as the true foundation of the economy. Chapter four rounds out the coverage with a focus on agriculture. Finally, in chapter five, the authors discuss the overall benefits of a “slow and curvy” management style in order to provide happiness, economic and social sustainability.